Pozycja i kompetencje rady programowej w spółce publicznej radiofonii i telewizji - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The powers of an advisory board are laid down in the currently binding Section 3, Art. 28a of the law. Said provision stipulates that the board passes resolutions concerning radio and television program (when gaining a majority of votes cast and the presence of at least a half of board members) and comprising the assessment of the level and quality of the running program and program schedule. This provision also stipulates that such resolutions are debated and decided by the supervisory board. It is rightfully observed in the doctrine that the advisory board is only an advising and consultative body for the corporation organs, and it only handles programming matters. The provision stipulates the principles and forms of operation of such bodies to only a limited extent.We also have to agree with the opinion that the powers of the program board are limited to program-related matters exclusively, that is to the selection of individual programs, proportions between them and general principles of radio and television operation. Thus, the board does not have a basis on which to take a stand in personnel, technical, business and legal matters, etc.